Interesting Learning Methods Innovation For Early Childhood Through Market Day Activities - Annazmil Fayros Latifah; Hamid Patilima; Ria Oktafera; Esta Rahma Cahyani; Fitriah Sakinah; Sabariah; Ruslianti; Lilis Dewi Sartika Sianturi (International Conferences on Early Childhood Education Proceedings, 2024)
The attitude and mentality of an entrepreneur is active and creative, so he tries to show efforts to increase income from his business activities. The main values of entrepreneurship that are sought to be integrated into learning in early childhood are: independence, creativity, ability to take risks, leadership, action orientation and hard work. These entrepreneurial values are one way to realize the goals of TKIT Ummul QuroManokwari regarding learning numeracy literacy and financial literacy through playing in the market day activity program. Market day activities do not only focus on market day (buying and selling), but children learn about producing, packaging products and marketing them. The research method used is interactive qualitative research with case studies. This research aims to show the current situation regarding the cultivation of entrepreneurial values through play in the form of market day activities for early childhood at TKIT UmmulQuro Manokwari. The research results will be used as a way to instill entrepreneurial values from an early age, so that in the future they can create employment opportunities.